2014
DOI: 10.1371/journal.pone.0114447
|View full text |Cite
|
Sign up to set email alerts
|

The Eukaryotic Elongation Factor 1A Is Critical for Genome Replication of the Paramyxovirus Respiratory Syncytial Virus

Abstract: The eukaryotic translation factor eEF1A assists replication of many RNA viruses by various mechanisms. Here we show that down-regulation of eEF1A restricts the expression of viral genomic RNA and the release of infectious virus, demonstrating a biological requirement for eEF1A in the respiratory syncytial virus (RSV) life cycle. The key proteins in the replicase/transcriptase complex of RSV; the nucleocapsid (N) protein, phosphoprotein (P) and matrix (M) protein, all associate with eEF1A in RSV infected cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 34 publications
0
32
0
2
Order By: Relevance
“…It may be possible to overcome this restriction by targeting a host cell-derived cofactor of the complex that is likewise indispensible for RdRp activity. For instance, the human translation elongation factor eEF1A is known to be required for VSV RdRp transcriptase activity ( Das et al, 1998 ; Qanungo et al, 2004 ) and was recently shown to be critically involved also in RSV replication ( Wei et al, 2014 ). A general requirement of eEF1A and/or additional host factors for paramyxovirus RdRp activity is possible, but direct therapeutic targeting of, for instance, eEF1A will likely be prohibited by its central role in host protein synthesis.…”
Section: Development Of Antiviral Therapeuticsmentioning
confidence: 99%
“…It may be possible to overcome this restriction by targeting a host cell-derived cofactor of the complex that is likewise indispensible for RdRp activity. For instance, the human translation elongation factor eEF1A is known to be required for VSV RdRp transcriptase activity ( Das et al, 1998 ; Qanungo et al, 2004 ) and was recently shown to be critically involved also in RSV replication ( Wei et al, 2014 ). A general requirement of eEF1A and/or additional host factors for paramyxovirus RdRp activity is possible, but direct therapeutic targeting of, for instance, eEF1A will likely be prohibited by its central role in host protein synthesis.…”
Section: Development Of Antiviral Therapeuticsmentioning
confidence: 99%
“…In fact, EF1α assists replication of many RNA viruses, such as the respiratory syncytialvirus (RSV). In this case, down-regulation of EF1α restricts the expression of viral genomic RNA and the release of infectious virus (Wei, et al 2014); in parasites, EF1α has also been implicated in pathogenesis (Nandan and Reiner 2005) and host cell invasion (Matsubayashi, et al 2013).…”
Section: Implications For Infection Biologymentioning
confidence: 99%
“…Multiple catalytic centers present in the L protein and a number of essential protein-protein interactions between viral proteins such as L and P and P-L and the encapsidated RNP template and viral polymerase components and mandatory host co-factors such as the human translation elongation factor eEF1A (108) provide a multitude of candidate druggable targets for small-molecule inhibition. A frequent problem especially of allosteric polymerase blockers is a narrow indication spectrum, however, restricting potent antiviral activity to a specific family member or pathogens of a single genus within the family (109, 110).…”
Section: Antiviral Strategies Targeting Pneumo- and Paramyxovirus Polmentioning
confidence: 99%